Simulation of Illumination and Wind Conditions for Green and Fed Cities Using CFD Software - Tkachenko, Tetiana; Viktor Mileikovskyi; Maryna Kravchenko; Viktoriia Konovaliuk (My University, 2023)
To avoid ecological catastrophe, most cities are moving toward green building. The important component is greening – conventional and green structures. Urban agriculture is a very prospective direction. Green roofs, terraces, and rooftop greenhouses are the most promising places for growing. This solves multiple tasks: heat loss recovery for planting (for rooftop greenhouses), additional thermal insulation, optimized logistics, increasing pollinator populations, avoiding pests, etc. In different-height districts, there are problems with natural illumination and winds. No good urban wind theory has been developed. The winds can be simulated in CFD software using a 3D model of a district. Most of the software can simulate solar radiation for thermotechnical calculations only. It should be simulated in other special software. The approach to calculating solar radiation is proposed using CFD software without additional needs. The special material – "integrator" – should be added to the engineering database. Its thermotechnical properties can be set to obtain a temperature, numerically equal to the interesting parameter. Application is shown in an example of a different-height building with a green roof. The results show areas most favorable for growing photophilous and shadetolerant plants, and to place cleaning and phytoncidal plants for the maximum air quality in stagnation zones.
Keywords: Illumination; Wind Conditions; Green City; Fed City; 620.92:004.42